Mechanical strength and drying shrinkage properties of RCA concretes produced from old railway concrete sleepers using by a modified EMV method. (10th October 2018) - Yang, Sungchul; Lim, Yujin
Highlights: PC sleepers with maximum size of 20 mm aggregate were crushed into 25 mm RCAs. Modulus of elasticity of RCA concrete with modified EMV mix is comparable to that made with natural aggregate concrete. RCA concrete by modified EMV mix retains lower drying shrinkage strain, compared to the companion natural aggregate concrete. Use of coarse RCA produced from old PC sleepers is promising for structural concrete. Abstract: This study aims to assess the mechanical strength and shrinkage properties of recycled concrete aggregate (RCA) concretes produced from old railway pre-stressed concrete (PC) sleepers. PC sleepers with compressive strength of 50 MPa grade, originally manufactured with a maximum size of 20 mm coarse aggregate, were crushed into 25 mm RCAs. A total of six mixes were prepared for typical structural concrete, using the modified equivalent mortar volume (EMV) as well as the conventional ACI mix design method. Comparable values of the elastic modulus and drying shrinkage properties of RCA concrete were achieved from the test results, relative to those of the companion natural aggregate concrete. The use of RCA produced from old PC sleepers is thus proven to be promising when RCA production is targeted for coarse aggregate in structural concrete.